The Basic Non-violence Resistance Forms and Hidden Nationalism as Inner Insubordination to the Soviet Regime in Latvia in seventies and eighties - Zalite, Indulis (Genocidas ir rezistencija, 1997)
The non–violent resistance to the Soviet dictatorship by various national groups in Latvia had common and different features. For Latvians, the idea of Latvian independence was the most important, whereas for Jews and Germans the most important was the struggle for the opportunity to leave for their ethnic homeland. Even in the Baltic Military District in the second half of the 1980s, there were open manifestations of nationalism. Taking together the data from the former LKP party archive and the information from ASIO Delta Latvia, it can be said that between 5 and 12 anti–Soviet or nationalist groups would be liquidated in the Latvian SSR each year. This statistical spread of anti–Soviet activities probably depended on the perception of anti–Soviet and/or nationalist activities during the various periods of communist Soviet rule and on the political leadership of the time. Of particular concern to the authorities were the groups and factions involving young people.